Perancangan dan Implementasi Sistem Penugasan Pegawai Pada Dinas Ketahanan Pangan Dengan Metode Hungarian - Arjon Samuel Sitio (STMIK Pelita NUsantara, 2016)
This study discusses employee performance organization that aims to know the relationship and the influence between the two. A supervisor of food security gives duties to his employees on every allocation such as the allocation of serbajadi subdistrict, dolok masihul, berohol and banyan cape. The quality of outcomes and the number of assigned allocations varies, indicating the costing, timing and quality of the results of each allocation. The Hungarian method is a method that modifies rows and columns in an effectiveness matrix until there appears a single zero component in each row or column that can be selected as assignment allocation. To facilitate the assignment of employees, required a software that can process employee assignment data. Based on these problems, it is necessary to do the analysis so that the results can be obtained with the discovery of the necessary needs for software built. Analysis is done by analyzing the needs, users and facilities needed by the built software is really useful. Applications built using MySQL database and visual basic software 2008. Keywords: System assignment of employees, Hungarian, Descriptive research